Spółdzielnia europejska – analiza założeń nowej ustawy - Magdoń, Antoni (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: On the 22nd of July 2006 Polish Parliament passed a new European Cooperative Society Law which determines rules of setting up, organisation and activity of European Cooperative Society. European Cooperative Society is a legislative structure created to achieve aims typical for cooperative and has many characteristic features of trading partnerships – joint stock companies’ in particular. An appearing of the new form of running business activity – European Cooperative Society may have a positive influence on the situation on the labor market by reducing the unemployment rate because cooperatives create favourable conditions for social integration. They can create work places and create favourable conditions for economic growth without aspiring to generate profit in order to divide it among members. Running activity in the form of European Cooperative Society enables local societies to intensive co-operation with each other in EU and will permit to effective allocation on the labor market taking into consideration social factor.